PREDIKSI FAKTOR PEROLEHAN PADA RESERVOIR TIGHT GAS DENGAN ANALISIS SENSITIVITAS TERHADAP PARAMETER-PARAMETER HYDRAULIC FRACTURING DAN PRODUKSI - Rizki Fawzi, Machruzi
Currently, the energy demand in natural gas sector is increasing rapidly. Therefore, other natural gas sources, such as non-conventional gas, can be an alternative to increase gas production. One of the non-conventional gas sources is tight gas, but this non-conventional gas source is difficult to develop. Therefore advanced technology is necessary to develop and produce this source, such as horizontal wells, hydraulic fracturing, or multiwells production by well pad drilling method. The objective of this study is to predict the recovery factor of tight gas reservoir using sensitivity analysis of hydraulic fracturing and production parameters, and to predict the maximum recovery factor of tight gas reservoir. Those parameters are: amount of producing wells, amount of hydraulic fractures, half-length fracture, dimensionless fracture conductivity, and flowing bottom-hole pressure. Reservoir simulation is done by inputting the aforementioned parameters to predict the obtained recovery factor from tight gas reservoir. Obtained recovery factor then is being analysed to observe the effect of each inputted parameters to recovery factor. From the analysis, the most influencing parameter is, respectively, amount of producing wells, flowing bottom-hole pressure, amount of hydraulic fractures, halflength fracture, and dimensionless fracture conductivity. The maximum recovery factor of this tight gas reservoir, under maximum operation condition, is calculated at 97.70%. Empirical equation to predict the recovery factor by inputting the aforementioned parameters has been constructed, with the R-squared value of 97.10%. However, from the test results, that empirical equation is accurate only in an interval of flowing bottom-hole pressure; therefore more study is needed to make the optimum use of that empirical equation.